Investigation of the Protective Effects of Magnesium on Bupivacaine-Induced Toxicity at the Level of Colon Cell Culture - Ceren Önal; Kemal Tolga Saraçoğlu; Ayten Saraçoğlu; Beyza Nur Özkan; Eray Metin Güler; Gülten Arslan; Seçil Azime Karakuş; Yekbun Bulun; Tomasz Gaszynski; Pawel Ratajczyk (Biomedicines, 2024)
The primary objective of this in vitro study was to prevent the risk of toxicity associated with bupivacaine, widely used in clinical practice, by using magnesium (Mg), a readily available and cost-effective element, as an adjuvant. We hypothesized that Mg might exhibit a protective effect against cytotoxicity in a colon cell culture model under conditions of bupivacaine-induced LAST. Our secondary aim was to investigate its effect on genotoxicity, apoptosis, and iROS. CCD-18Co cells were used in our study. Control group (group C), Bupivacaine group (group B), Magnesium group (group M), and Bupivacaine+Mg group (group BM) were created. The viability of CCD-18Co cells incubated for 24 h in group C was determined to be 100%. These cells were evenly divided, and bupivacaine was administered to group B at concentrations of 5 to 300 μM. In group M, doses of Mg at 0.625 to 320 mEq were added. It was determined that the maximum viability was observed at a Mg dose of 40 mEq (p < 0.05). In group BM, bupivacaine was administered at the same concentrations in combination with Mg (40 mEq), and cell viability was measured. DNA damage, apoptosis, and iROS were assessed at concentrations of bupivacaine by administering 40 mEq Mg. In group B, viability decreased dose-dependently in CCD-18Co (p < 0.05, p < 0.01, p < 0.001). In group BM, the viability decreased in cells at increasing concentrations compared to group C (p < 0.05, p < 0.01, p < 0.001), but the viability was affected positively compared to group B (p < 0.05). In group B, DNA damage increased (p < 0.05, p < 0.001). In group BM, DNA damage increased (p < 0.05, p < 0.001). However, in group BM, DNA damage levels were reduced compared to group B (p < 0.05, p < 0.01). In group B, apoptosis increased (p < 0.05, p < 0.001); in group BM, apoptosis increased (p < 0.001) compared to group C. However, in group BM, apoptosis decreased compared to group B (p< 0.05). iROS increased in group B (p < 0.05, p < 0.01, p < 0.01) and group BM (p < 0.05, p < 0.01, p < 0.001) compared to the group C. However, in group BM, iROS decreased in comparison to group B (p < 0.05). In conclusion, Mg exhibits a protective effect against bupivacaine-induced toxicity.